PENYISIHAN WARNA PADA LIMBAH CAIR SASIRANGAN DENGAN ADSORPSI ZEOLIT DALAM FIXED-BED COLUMN - Andy Mizwar (Universitas Lambung Mangkurat, 2013)
A natural zeolite was used to investigate its adsorption capacity for the color from sasirangan textile wastewater in this experiment. This study aims to analyze the performance of zeolite bed height and flow rate arrangements at constant pH and temperature on the effectiveness of color removal in sasirangan wastewater, and to study the adsorption kinetics system that occurs in the process. In this study, color adsorption analyzed with a continuous flow of wastewater (flow rate of 20 ml/min, 40 ml/min, and 80 ml/min) into a 2.5 inch diameter column adsorption by zeolite 10 cm, 30 cm, and 60 cm high. Treated water sampling conducted every 10 minutes until the zeolite saturated. The results showed that the performance of the flow rate setting is inversely proportional to the effectiveness of color removal, and otherwise adsorbent bed height setting is directly proportional to the effectiveness of color removal in sasirangan wastewater. The highest percentage removal amounted to 48,30% at a flow rate of 20 ml/min and 30 cm bed height of zeolite, while the lowest is 7,02% at a flow rate 40 ml / min and 10 cm bed height of zeolite. In this study, Thomas Model was fitted to describe the pattern of color adsorption by zeolite with a maximum adsorption capacity of 18,758 mg/g.